Bioluminescence‐driven optogenetic activation of transplanted neural precursor cells improves motor deficits in a Parkinson's disease mouse model. Issue 3 (25th March 2018) - Zenchak, Jessica R.; Palmateer, Brandon; Dorka, Nicolai; Brown, Tariq M.; Wagner, Lina‐Marie; Medendorp, William E.; Petersen, Eric D.; Prakash, Mansi; Hochgeschwender, Ute
Abstract: The need to develop efficient therapies for neurodegenerative diseases is urgent, especially given the increasing percentages of the population living longer, with increasing chances of being afflicted with conditions like Parkinson's disease (PD). A promising curative approach toward PD and other neurodegenerative diseases is the transplantation of stem cells to halt and potentially reverse neuronal degeneration. However, stem cell therapy does not consistently lead to improvement for patients. Using remote stimulation to optogenetically activate transplanted cells, we attempted to improve behavioral outcomes of stem cell transplantation. We generated a neuronal precursor cell line expressing luminopsin 3 (LMO3), a luciferase‐channelrhodopsin fusion protein, which responds to the luciferase substrate coelenterazine (CTZ) with emission of blue light that in turn activates the opsin. Neuronal precursor cells were injected bilaterally into the striatum of homozygous aphakia mice, which carry a spontaneous mutation leading to lack of dopaminergic neurons and symptoms of PD. Following transplantation, the cells were stimulated over a period of 10 days by intraventricular injections of CTZ. Mice receiving CTZ demonstrated significantly improved motor skills in a rotarod test compared to mice receiving vehicle. Thus, bioluminescent optogenetic stimulation of transplanted neuronal precursor cells shows promising effects in improving locomotor behavior in the aphakia PD mouse model and encourages further studies to elucidate the mechanisms and long‐term outcomes of these beneficial effects. Abstract : Stimulation of transplanted neuronal precursor cells through activation of channelrhodopsin by luciferase emitted light improves motor behavior in Parkinson's disease mice. Such bioluminescent optogenetic stimulation during the early initial phase after striatal transplantation seems beneficial for function of transplanted cells.